High Dose Immunoglobulin (IVIG) May Reduce the Incidence of Langerhans Cell Histiocytosis (LCH)-Associated Central Nervous System Involvement - Imashuku, Shinsaku (CNS & Neurological Disorders - Drug Targets, 2009)
Diabetes insipidus and neurodegenerative disease are the two major central nervous system (CNS) complications of Langerhans cell histiocytosis (LCH). Once it has developed, diabetes insipidus is permanent, while the outcome of neurodegenerative disease is dismal. The development of these CNS-LCH complications is closely correlated with “CNS-risk” organ involvement, namely, the presence at diagnosis of LCH lesions in cranio-facial areas. Based on recent data showing the beneficial effects of intravenous immunoglobulin (IVIG) treatment on inflammatory diseases of the CNS, we are currently testing whether monthly IVIG treatment (0.4 g/kg/dose) can alleviate the progression of neurodegenerative disease in LCH patients. We also hypothesize that the incidence of CNS complications could be reduced by the prophylactic administration of high dose IVIG therapy (2 g/kg/dose), combined with conventional induction chemotherapy, that is provided before CNS lesions are detected in “CNS-risk”-LCH patients.
Keywords: Intravenous immunoglobulin